The Effect of Facilitator Gender on the Effectiveness of Adolescent Reproductive Health Education: A Literature Review - Vania, Florentina Kirana; Prabamurti, Priyadi Nugraha; Indraswari, Ratih (Journal of Public Health for Tropical and Coastal Region, 2024)
Abstract Introduction: Sex education is a prevention measure to decrease juvenile delinquency. However, the implementation of sex education runs insufficiently and it is influenced by various factors. Of those, gender is one of the factors. This study shows the results of literature reviews regarding the relationship between facilitators and the effectiveness of sex education in adolescents aged 13-19 years.Methods : This research method used a literature review, by screening literature from 4 databases; Google Scholar, Pubmed, Science Direct, and Scopus. The PRISMA flow chart was used to show each step eligibility criteria of article selection.Results: This study found 6 journals that match the inclusion criteria. There were 5 articles that show a relationship between the gender of e-facilitators and the effectiveness of sex education in adolescents aged 13-19 years, while 1 article did not show a relationship because of an imbalance in the sample between male facilitators (24.5%) and women facilitators (75.5%).Conclusion: This review highlighted that implementing class separation based on sex (single-sex education) is one of best strategies to increase the effectiveness of reproductive health education for adolescents aged 13- 19 years. Thus, it is also suggested for Health Office or NGO to adopt a separate class system based on gender.